Is foliar enrichment of pea plants with iodine and selenium appropriate for production of functional food?. (30th November 2018) - Jerše, Ana; Kacjan Maršić, Nina; Kroflič, Ana; Germ, Mateja; Šircelj, Helena; Stibilj, Vekoslava
Highlights: Pea plants did not show signs of stress after foliar treatment with I and Se. Significant enrichment of pea seeds with iodine when applied as I(–I) Nutritionally important levels of Se were achieved in pea seeds in all experiments. Diverse effects of I on Se uptake and vice versa in seeds and other parts of plant. Abstract: Pea ( Pisum sativum L.) plants were sown in a field and foliar sprayed at blooming stage with solutions of different forms of iodine (I) – I − and IO3 − and selenium (Se) – SeO3 2− and SeO4 2− . The possibility of enrichment of pea seeds to nutritionally important levels of both elements and their distribution through the plant parts were studied. To evaluate stress caused by application of I and Se, some morphological, physiological and biochemical characteristics were determined. The results showed elevated concentrations of both elements in all parts of pea plants. In seeds, I content was more than 6-fold higher, while Se content was up to 12-fold higher than in control plants. Although the plants were in good condition, some differences in pod characteristics and electron transport system activity were observed. Glutathione content was not affected by any treatment and only the I −  + SeO4 2− combination decreased the amount of anthocyanins in plants.